Global class : how the world's fastest-growing companies scale globally by focusing locally - McDaniel, Aaron; Wehage, Klaus (Ascent Audio, 2022)
The business world has changed and to stay ahead companies have to think, operate, and scale differently. Companies need to adopt a new mindset and build distributed teams with a unique set of skills to succeed in new markets. A new strategic approach and revision to the agile methodology are necessary to better balance the need to localize with the complexity that localization creates. To date, business leaders have had to learn how to scale globally the hard way-through trial, error, and failure-since no guidebook existed to light the way ... until now. Enter Global Class. Global Class is the playbook that teaches you how to build teams, manage a diverse international footprint, and balance cultural differences to scale globally by focusing locally. Through case studies and insights from more than 250 of the world's fastest growing companies, Aaron McDaniel and Klaus Wehage illuminate what this new class of business ("Global Class Companies") does to succeed, and who are the catalysts of their growth ("Interpreneurs") and how they do it. From market entry to international growth, Global Class introduces a comprehensive tool kit of practical frameworks that provide a blueprint for how to build and manage a global business